2004
DOI: 10.3354/meps273239
|View full text |Cite
|
Sign up to set email alerts
|

Individual behavior and emergent properties of fish schools: a comparison of observation and theory

Abstract: Polarity, group velocity, and inter-individual spacing are characteristics of fish schools that strongly affect individual school members. However, these characteristics are group-level 'emergent properties': collective outcomes of behavioral interactions among members, not under direct control of any single member. The relationships between members' behaviors and the emergent group properties they produce are complex and poorly understood. In this study, we quantified 3D trajectories of all individual fish wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
148
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(173 citation statements)
references
References 41 publications
10
148
1
2
Order By: Relevance
“…In particular, a series of simulation studies have shown that the mean speed of an individual could be considered as an emergent property as well [51,69,74]. In self-propelled particles models, fixed speed implies a direct proportionality between polarization and mean speed of the school.…”
Section: Social Forces Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a series of simulation studies have shown that the mean speed of an individual could be considered as an emergent property as well [51,69,74]. In self-propelled particles models, fixed speed implies a direct proportionality between polarization and mean speed of the school.…”
Section: Social Forces Modelsmentioning
confidence: 99%
“…An intensification of the modelling and simulation effort over the last decades yield an important collection of models and studies, shedding some light on the complex interplay between the individual and school levels, and subsequent methodological and conceptual issues [51].…”
Section: From Individual To Collective Behaviourmentioning
confidence: 99%
“…Recent break throughs in remote quantification of physical landscapes [58 60] and 3D imaging [29] should be especially helpful for these questions. Second, collective behavior in animal groups [1,26,33,38,40,43,45,62,82,83], including understanding how information about the physical and biological environment transfers between individuals. Generally, this research centers on intraspecific groups comprising large numbers of similar sized individuals.…”
Section: Box 1 Ecological Insights From Automated Image-based Trackingmentioning
confidence: 99%
“…Tracking systems designed for 2D can provide some resolution for behavior in a third spatial dimension [34), but ultimately developers must produce tracking systems that can successfully track large numbers of animals in 3D space (Movie S8 in the supplementary material online). Tracking unconstrained flying or swimming animals can be achieved in several ways, but most often multiple cameras are employed [18,29,[35][36][37][38][39][40][41][42][43][44][45] (Movie S6, Movie 88, and Movie S22 in the supplementary material online). Although only two calibrated cameras taking images of the same point in space are required for triangulation, information from additional cameras can incrementally improve localization, especially if some cameras are limited by occlusion or low contrast [18) .…”
Section: Tracking In Three Dimensionsmentioning
confidence: 99%
“…The second approach, consisting of the development of mathematical models by computer scientists (Reynolds, 1987), by biologists (Parrish, Viscido, & Grünbaum, 2002;Suzuki, Tsumonu, & Hiraishi, 2003;Viscido, Parrish, & Grünbaum, 2004), or by physicists (Grégoire & Chaté, 2004;Vicsek, Czirók, Ben-Jacob, Cohen, & Shochet, 1995;Vicsek, Czirók, Farkas, & Helbing, 1999) is artificial. It requires a comparison with empirical results to validate and determine the degree of validity for each model.…”
mentioning
confidence: 99%